2014
DOI: 10.1177/001440291408000205
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of ADHD in Children with Learning Disabilities or Emotional Disturbances

Abstract: Despite the high prevalence of comorbidity between attention deficit/hyperactivity disorder (ADHD) and learning disabilities (LD) or emotional disturbances (ED), few studies have examined the long-term effects of these comorbid relationships on student outcomes. We estimated the longitudinal academic, social, and behavioral outcomes in children with LD or ED comorbid with or without ADHD in a nationally representative sample of students receiving special education. We found that children with LD and ADHD had l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 48 publications
0
14
0
2
Order By: Relevance
“…Social and emotional well-being of adolescents identified with disabilities includes challenging behaviors, inattention, and impulsivity, so it was not surprising that transition plans for adolescents with ED and ADHD/OHI were significantly more likely to include goals in these areas, setting them apart from the transition plans for adolescents with LD. Yet, students with LD, and in particular those with LD who also have ADHD characteristics, struggle with social skills (Kavale & Mostert, 2004; Wei, Yu, & Shaver, 2014), making this distinction somewhat surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Social and emotional well-being of adolescents identified with disabilities includes challenging behaviors, inattention, and impulsivity, so it was not surprising that transition plans for adolescents with ED and ADHD/OHI were significantly more likely to include goals in these areas, setting them apart from the transition plans for adolescents with LD. Yet, students with LD, and in particular those with LD who also have ADHD characteristics, struggle with social skills (Kavale & Mostert, 2004; Wei, Yu, & Shaver, 2014), making this distinction somewhat surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Although the core deficit of ADHD and DD was believed to be attention and language, respectively (Weiler et al, 2002), some studies have reported that children with ADHD also showed deficits in letter or word recognition (Wei et al, 2014;Lúcio et al, 2017;Mohammadhasani et al, 2019) and that DD children also demonstrated deficits in visual attention or response inhibition (Willcutt et al, 2000;Martin et al, 2006;Vidyasagar and Kristen, 2010). These results may provide evidence of the shared cognitive deficit model.…”
Section: Introductionmentioning
confidence: 99%
“…Oleh karena itu pendidikan calon guru khusus berdasarkan kebutuhan anak (Sabornie et al, 2006) dan pemenuhan kebutuhan anak perlu perlu menjadi bahan pertimbangan. Pemberian label yang keliru rentan terjadi karena proses penegakan diagnosis yang kurang didukung ahli juga tidak akan menjadi kendala bila guru dipersiapkan bukan berdasarkan kekhususan anak (Schnoes, Reid, Wagner, & Marder, 2006;Xin Wei, Yu, & Shaver, 2014). Hal yang paling mendasar yang menjadi alasan pergeseran fokus penyiapan guru adalah kebermaknaan layanan untuk anak berkebutuhan khusus berdasarkan pemenuhan kebutuhan belajar mereka (Hallahan & Kauffman, 1977).…”
Section: Pembahasanunclassified